Self-Explanation as a Teaching Technique: Literature Review for Elementary School Education - Fitrah Marhamah; Aqilah Nadya Shofwah; Cristin Novstasya Saragih; Rahmilawati Ritonga (Jurnal Pengabdian Nusantara, 2026)
Self-explanation is one of the learning techniques that gives space for students to explain the material content again with their own words, either orally or in writing. This technique is considered relevant for basic education because it can help children recognize their way of thinking, check their understanding, and strengthen the relationships between concepts. This article presents a literature review on the application of self-explanation in the context of learning in elementary schools based on research from the last five years. This literature study traces various national and international articles through a gradual selection process and thematic analysis to find patterns of findings related to the effectiveness of this technique. The results of the study show that self-explanation not only increases conceptual understanding, but also strengthens metacognitive abilities, learning independence, and the quality of student interaction with the material. This technique has proven relevant for various subjects, such as reading, mathematics, and science. This article is expected to provide a comprehensive picture of the potential of self-explanation as an alternative learning strategy that is more reflective and student-centered in elementary education.